2011
DOI: 10.1093/nar/gkr1236
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of DNA binding and gene regulation by homologous nucleoid-associated proteins IHF and HU in Escherichia coli K12

Abstract: IHF and HU are two heterodimeric nucleoid-associated proteins (NAP) that belong to the same protein family but interact differently with the DNA. IHF is a sequence-specific DNA-binding protein that bends the DNA by over 160°. HU is the most conserved NAP, which binds non-specifically to duplex DNA with a particular preference for targeting nicked and bent DNA. Despite their importance, the in vivo interactions of the two proteins to the DNA remain to be described at a high resolution and on a genome-wide scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
172
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(198 citation statements)
references
References 61 publications
(111 reference statements)
21
172
0
5
Order By: Relevance
“…A completely new perspective on intragenic binding of H-NS was the finding that these loci often correspond to Ogasawara et al, 2010]; high-affinity binding sites determined by DNA footprint assays are indicated by a line superimposed on the ChIP-seq binding peaks. Binding sites determined by DNA footprint assays for FIS and IHF are indicated by boxes along the linear chromosome, whereas binding regions detected by ChIP-seq [Kahramanoglou et al, 2011;Prieto et al, 2012] are indicated by bars parallel to the chromosome. sites of spurious transcription (arising from weak promoters) of noncoding and antisense RNAs or due to inefficient Rho-dependent termination [Peters et al, 2012;Purtov et al, 2014;Saxena and Gowrishankar, 2011;Singh and Grainger, 2013].…”
Section: Intragenic-specific Bindingmentioning
confidence: 99%
“…A completely new perspective on intragenic binding of H-NS was the finding that these loci often correspond to Ogasawara et al, 2010]; high-affinity binding sites determined by DNA footprint assays are indicated by a line superimposed on the ChIP-seq binding peaks. Binding sites determined by DNA footprint assays for FIS and IHF are indicated by boxes along the linear chromosome, whereas binding regions detected by ChIP-seq [Kahramanoglou et al, 2011;Prieto et al, 2012] are indicated by bars parallel to the chromosome. sites of spurious transcription (arising from weak promoters) of noncoding and antisense RNAs or due to inefficient Rho-dependent termination [Peters et al, 2012;Purtov et al, 2014;Saxena and Gowrishankar, 2011;Singh and Grainger, 2013].…”
Section: Intragenic-specific Bindingmentioning
confidence: 99%
“…Lrp forms octomeric structures around which DNA winds, similarly to DNA wrapping around histones (de los Rios and Perona 2007). HU, IHF, Lrp, DnaA, and IciA are also global transcription regulators (Bouvier et al 1998;Oberto et al 2009;Prieto et al 2012).…”
mentioning
confidence: 99%
“…Wild-type HU has a significant impact on gene expression at both the transcriptional and posttranscriptional levels [Mangan et al, 2011;Oberto et al, 2009;Prieto et al, 2012], the latter reflecting its RNA binding activity [Balandina et al, 2001;; HU also possesses efficient single-stranded DNA binding activity [Kamashev et al, 2008]. Thus, HU is a highly versatile protein, acting in an architectural mode to impose structure on the nucleoid while simultaneously influencing transcription and translation.…”
Section: Nucleoid Shape-determining Protein Humentioning
confidence: 99%